ChemInform Abstract: The Two‐Dimensional Anion [Sb6Se10]2‐: Solvothermal Synthesis, Crystal Structure, and Properties of an Iron Selenidoantimonate(III) [Fe(phen)3]Sb6Se10. Issue 34 (4th August 2016) - Shen, Yali; Liu, Yun; Liu, Shuzhen; Sun, Peipei; Tang, Chunying; Han, Jingyu; Jia, Dingxian
Abstract: [Fe(phen)3 ]Sb6 Se10 is prepared by solvothermal reaction of a 1:2:6 molar mixture of Fe, Sb, Se with phen and DABCO in MeOH/H2 O (3:1) mixed solvent (autoclave, 150 °C, 6 d).